A location–inventory supply chain problem: Reformulation and piecewise linearization. (December 2015) - Diabat, Ali; Theodorou, Effrosyni
Highlights: We study a two-echelon inventory management problem with multiple retailers. The problem is formulated as an MINLP. We propose an equivalent formulation with fewer non-linear terms. We use piecewise linearization to transform the resulting MINLP to an MIP. The new approach is capable of providing almost the same solutions obtained by LR. Abstract: In this paper, we study a two-echelon inventory management problem with multiple warehouses and retailers. The problem is a natural extension to the well-known one-warehouse multi-retailer inventory problem. The problem is formulated as a mixed integer non-linear program such that its continuous relaxation is non-convex. We propose an equivalent formulation with fewer non-linear terms in the objective function so that the continuous relaxation of the new model is a convex optimization problem. We use piecewise linearization to transform the resulting MINLP to a mixed integer program and we solve it using CPLEX. Through numerical experiments, we compare the solutions obtained by solving the new formulation using CPLEX with two previously published Lagrangian relaxation based heuristics to solve the original mixed integer non-linear program. We demonstrate that the new approach is capable of providing almost the same solutions without the need of using specialized algorithms. This important contribution further implies that additional variants of the problem, such as multiple products, capacitated warehouses and routing, can be added to result in a problem that will again be solvable by commercial optimization software, while the respective Lagrangian heuristics will fail to solve such variants or extended problems.